Ecological study of periphyton diversity in crenic habitat of Sahashradhara (Garhwal Himalayas, India) - Chauhan, Anita; Sharma, Ramesh C. (International Journal of Environment, 2016)
A maiden attempt has been made to present a biodiversity of periphyton of the Sahashradhara springs, a group of one thousand springs and one of the most important clusters of limnocrenes and rheocrenes springs located in Doon Valley of Garhwal-Himalayas. The environmental monitoring of periphyton community of Sahashradhara springs was carried out for one complete annual cycle (October 2011-September 2012). Annual percentage composition of periphyton revealed that major contribution was represented by Bacillariophyceae (68-70%) followed by Chlorophyceae (26-28%) and Myxophyceae (3-5%). A total of 29 species of periphyton were recorded from different springs of Sahashradhara. A significant correlation between diversity of periphyton and environmental parameters- temperature, turbidity, conductivity, dissolved oxygen, free CO2, alkalinity, FPOM and CPOM was observed. Regression analysis was performed between density of periphyton and physico-chemical variables, which revealed that temperature, conductivity, alkalinity, CO2, TDS, CPOM and FPOM were found to have strong influence on the density and diversity of periphyton of Sahashradhara springs.International Journal of Environment Vol. 5 (1) 2016,  pp: 79-95